Many facets of reasoning under uncertainty, inconsistency, vagueness, and preferences: a brief survey - Kern-Isberner, G; Lukasiewicz, T (Springer Berlin Heidelberg, 2017)
In this paper, we give an introduction to reasoning under uncertainty, inconsistency, vagueness, and preferences in artificial intelligence (AI), including some historic notes and a brief survey to previous approaches.